Implementation of classroom-based assessment in Malaysia - Tan, Tong Hock; Mohd Ayub, Ahmad Fauzi; Mohd Shah, Manisah; Ahamed, Ajurun Begum (International Journal of Academic Research in Progressive Education and Development, 2022)
Classroom-based Assessment (CBA) was officially established and introduced to focus on pupils' learning's holistic development and eradicate exam-oriented learning. Albeit the specific circular was issued in 2017, teachers in schools still lacked the skills and confidence in its implementation. The teachers presumed that the CBA is merely a teaching and assessment task detached from the existing teaching and learning. The apprehension was formed due to insufficient information on the implementation of the CBA. The practical implementation of CBA requires a comprehensive and systematic planning stage, followed by the preparation, implementation, and reporting stage. Henceforth, the Ministry of Education conducted workshops and intensive CBA training for headteachers and school principals to understand CBA implementation procedures. Based on the kind hand-in-hand, school leaders are deemed responsible for disseminating the CBA knowledge and skills acquired to teachers in their respective schools for implementation. However, the extent to which the implementation of CBA would be a triumph is yet to be substantiated. Subsequently, this study suggests a comprehensive CBA framework model to stakeholders by guiding their teachers in understanding the concepts and skills of CBA. This model, too, could assist teachers and boost their confidence during the implementation of CBA in the classroom.